Folklore in motion : Texas travel lore - Untiedt, Kenneth L., 1966- (Publications of the Texas Folklore Society, 2007)
The adventurous spirit of Texans has led to much travel lore, from stories of how ancestors first came to the state to reflections of how technology has affected the customs, language, and stories of life "on the go." This work contains traditional "Gone to Texas" accounts and articles about people or methods of travel from days gone by.